2016
DOI: 10.21890/ijres.05662
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Scientific Creativity of Gifted Students Through Project-Based Activities

Abstract: In this research, it is aimed to identify the scientific creativity of gifted students through project-based activities. In accordance with this purpose, a study has been carried out with 13 gifted students studying in third and fifth grade. In the study, students have been informed about the project development stages and they have been asked project designs that would facilitate the daily life. Following the project designs, semi-structured interviews with the students and teacher observations in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
0
20
0
5
Order By: Relevance
“…Some authors elected to include multiple definitions of creativity (Pitri, ), which made it difficult to pinpoint the study's contributions to specific creativity theories. Emphasis on cognitive components included divergent thinking, convergent thinking, fluency, and flexibility (e.g., Karademir, ). Problematically, Robson and Rowe () used a standard creative thinking framework that conflated “imagination” with “creativity,” which they then proceeded to explain in terms such as originality and novelty, and even critical thinking.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors elected to include multiple definitions of creativity (Pitri, ), which made it difficult to pinpoint the study's contributions to specific creativity theories. Emphasis on cognitive components included divergent thinking, convergent thinking, fluency, and flexibility (e.g., Karademir, ). Problematically, Robson and Rowe () used a standard creative thinking framework that conflated “imagination” with “creativity,” which they then proceeded to explain in terms such as originality and novelty, and even critical thinking.…”
Section: Resultsmentioning
confidence: 99%
“…Critical incident sampling, where a case or participant is sampled as an important example of a construct (Patton, ), was used in one article; surveys and interviews led to the selection of three students for classroom observations based on their use of creativity in science (Meyer & Lederman, ). Other studies sampled students identified as gifted (e.g., Karademir, ), and then proceeded to conduct observations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations